The DNA replication priming protein, PriA, is required for homologous recombination and double-strand break repair. - Kogoma, T (1996)
The PriA protein, a component of the phiX174-type primosome, was previously shown to be essential for damage-inducible DNA replication in Escherichia coli, termed inducible stable DNA replication. Here, we show that priA::kan null mutants are defective in transductional and conjugational homologous recombination and are hypersensitive to mitomycin C and gamma rays, which cause double-strand breaks. The introduction of a plasmid carrying the priA300 allele, which encodes a mutant PriA protein capable of catalyzing the assembly of an active primosome but which is missing the n'-pas-dependent ATPase, helicase, and translocase activities associated with PriA, alleviates the defects of priA::kan mutants in homologous recombination, double-strand break repair, and inducible stable DNA replication. Furthermore, spa-47, which was isolated as a suppressor of the broth sensitivity of priA::kan mutants, suppresses the Rec- and mitomycin C sensitivity phenotypes of priA::kan mutants. The spa-47 suppressor mutation maps within or very near dnaC. These results suggest that PriA-dependent primosome assembly is crucial for both homologous recombination and double-strand break repair and support the proposal that these processes in E. coli involve extensive DNA replication.